THE BORDER BALLADS: HISTORY AND CULTURE - Eldorbek Erkin og’li Khamitov; Turdimuratova Mexribanu Janabaevna (Ta’lim innovatsiyasi va integratsiyasi, 2026)
Abstract The Border Ballads, which developed along the Anglo-Scottish border during the late medieval and early modern periods, constitute a distinctive and culturally rich part of traditional folk literature. Rooted in regions frequently affected by conflict, raids, and political instability, these ballads reflect the historical realities and social dynamics of border communities. This study explores the history, cultural identity, and literary features of Border Ballads, highlighting how their structure and style convey both narrative content and communal values. In terms of ballad structure, Border Ballads commonly employ quatrains with alternating iambic tetrameter and trimeter, combined with straightforward rhyme schemes such as ABCB or ABAB. The use of repetition, refrains, and incremental repetition supports oral transmission, ensuring that the stories could be memorized and passed down through generations. Stylistically, these ballads are marked by direct, economical language, vivid dialogue, and action- driven storytelling. Symbolism, imagery inspired by natural and martial elements, and understatement further enhance the narrative, all while maintaining accessibility for a largely oral audience. The historical context of the Anglo-Scottish border deeply influences the themes of these ballads, which often portray feuds between families, border reivers, loyalty, honor, love, betrayal, revenge, and survival under harsh social and political conditions. Through these narratives, the ballads preserve collective memory, transmit moral codes, and shape the cultural identity of border communities. They exemplify the intertwining of historical fact and artistic interpretation, demonstrating how oral tradition can convey both social reality and literary artistry. In conclusion, Border Ballads occupy a unique position in folk literature, blending historical context, narrative creativity, and cultural expression. Their consistent ballad structure, memorable stylistic features, and thematic focus on human experience and border life underline their significance as both literary works and cultural records. By examining these aspects, this study emphasizes the enduring role of oral tradition in shaping collective memory, narrative style, and regional cultural identity.